Islam Nusantara and Non-Western Psychological Resilience: Lessons from Indonesian Boarding School (Pesantren) Culture - Furqon, Mohamad; Ayungtyas, Ira Palupi; Arifiani, Rina; Minho, Kim; Tu, Nguyen Minh (Yayasan Minang Darussalam, 2025)
This article explores the relationship between Islam Nusantara and non-Western psychological resilience, focusing on the traditions developed in Indonesian boarding schools (pesantren). In a global context often influenced by Western psychological paradigms, Indonesia presents a unique approach to building psychological resilience through religious teachings and practices deeply rooted in local culture. This study identifies how pesantren, as traditional Islamic educational institutions, play a significant role in shaping individual and community resilience through the teaching of spiritual, social, and cultural values derived from Islam Nusantara. Using a qualitative approach, this study analyzes pesantren practices that promote mental resilience, such as the cultivation of strong faith, the strengthening of social bonds, and role-model-based learning. The findings suggest that pesantren offers a model of psychological resilience that integrates local wisdom with Islamic teachings, distinguishing it from Western psychological approaches that focus more on the individual. This article also emphasizes the importance of recognizing non-Western psychological approaches in promoting mental well-being, particularly within Muslim communities in Indonesia.